2016
DOI: 10.1186/s12885-016-2469-9
|View full text |Cite
|
Sign up to set email alerts
|

ColoNav: patient navigation for colorectal cancer screening in deprived areas – Study protocol

Abstract: BackgroundThe mass colorectal cancer screening program was implemented in 2008 in France, targeting 16 million French people aged between 50 and 74. The current adhesion is insufficient and the participation rate is even lower among the underserved population, increasing health inequalities within our health care system. Patient Navigation programs have proved their efficiency to promote the access to cancer screening and diagnosis.Methods/DesignThe purpose of the study is to assess the implementation of a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…The COLONAV study (2,4) found that peer navigators, unaffiliated with healthcare structures, succeeded in increasing participation in colorectal cancer screening in disadvantaged geographical areas. As opposed to studies in other countries, this study showed that deprived communities in France were inadequately identified using ethnicity or residential neighbourhood.…”
Section: Trial Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The COLONAV study (2,4) found that peer navigators, unaffiliated with healthcare structures, succeeded in increasing participation in colorectal cancer screening in disadvantaged geographical areas. As opposed to studies in other countries, this study showed that deprived communities in France were inadequately identified using ethnicity or residential neighbourhood.…”
Section: Trial Resultsmentioning
confidence: 99%
“…In France, participation in screening programs (SP) for either colorectal or breast cancer does not meet objectives and varies significantly according to individuals' socioeconomic status (1,2). Interventions to increase participation in cancer SP have been developed and evaluated by our research team.…”
Section: Introductionmentioning
confidence: 99%
“…In reality most realist evaluations in health are qualitative in nature and any quantitative analysis focuses on outcomes, tending to either be descriptive or use hypothesis testing to assess statistical significance before and after intervention implementation [ 28 ]. Few use more advanced statistical modelling techniques, such as interrupted time series or regression [ 29 , 30 ]. However, these techniques are used to compare outcomes across time or in different groups, rather than explore the relationship between context, mechanism and outcome configurations.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by an institutional review board (Ethical Committee of Saint Etienne University Hospital, 10 th of January 2013), which waived the need for signed informed consent according to French law, since the study involved healthy people and proposed no treatment. The study protocol has been detailed elsewhere [20].…”
Section: Methodsmentioning
confidence: 99%